PEMANFAATAN TEKNOLOGI AI UNTUK PENINGKATAN KREATIVITAS ANAK ASUH YAYASAN AS-SYAMSURIYAH JAKARTA - Yusnia Budiarti; Ahmad Setiadi; Norma Yunita; Wahyutama Fitri Hidayat (Indonesian Community Service Journal of Computer Science, 2025)
Community service activities with the theme of Increasing Creativity Using AI at the As-Syamsuriyah Foundation aim to enhance the skills of the children under the care of the As-Syamsuriyah Foundation in utilizing Artificial Intelligence (AI) technology through visual arts in the form of videos that can be used for effective documentation and publication. In this digital era, AI offers great potential to boost human creativity, but its use must be carried out carefully and responsibly. By understanding and addressing ethical challenges, we can ensure that AI becomes a partner that enriches the creative world, rather than a threat that undermines it. Wise implementation of AI allows humans to continue to evolve, creating works that harmoniously blend technology and human touch. This training includes visual arts in the form of videos utilizing AI technology that can be used for documentation and publication. Participants will learn to utilize AI using software to create easily accessible animation videos suitable for the foundation's documentation needs. This activity is expected to help the foundation's children improve their creativity using AI while still paying attention to ethical aspects. The output of this community service activity will be in the form of articles in print or electronic media, increased knowledge and skills of the partners.